1997
DOI: 10.1159/000456983
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Neutralizing gp120 Monoclonal Antibodies to Prevent HIV Infection of Choriocarcinoma-Derived Trophoblasts

Abstract: Although placental trophoblasts, the only fetal cells in direct contact with infectious maternal blood, can be infected with HIV, the precise cause for the low transmission rate of virus across the placental barrier is unknown. One of the most common conjectures is that maternal anti- HIV antibodies (Abs) contribute to the protection of the fetus. This hypothesis has been tested in vitro by infecting the CD4-negative placental trophoblast line, BeWo, with HIV-1 mg in the presence of serial dilutions of neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Hence, the role played by CD4 and coreceptors in HIV-1 entry into trophoblastic cells is still unclear, but it is reasonable to assume that CD4, CXCR4, and CCR5 are unlikely to play a significant role, because they are expressed at such low levels if present. In agreement with this, several groups have shown recently that CD4 is not required for HIV-1 infection in trophoblasts [27][28][29][30]. In this context, we developed 2 hypotheses.…”
supporting
confidence: 64%
“…Hence, the role played by CD4 and coreceptors in HIV-1 entry into trophoblastic cells is still unclear, but it is reasonable to assume that CD4, CXCR4, and CCR5 are unlikely to play a significant role, because they are expressed at such low levels if present. In agreement with this, several groups have shown recently that CD4 is not required for HIV-1 infection in trophoblasts [27][28][29][30]. In this context, we developed 2 hypotheses.…”
supporting
confidence: 64%
“…The phenomenon of enhancement of HIV infection by HIVspecific antibodies surfaced as early as 1988 and has been regularly reported by reputable investigators in dozens of labs around the world (53,66,133). Our own experience has shown that, depending on the assay conditions and type of target cells, even the most potent neutralizing antibodies can behave like infectionenhancing antibodies (19). For this reason, standard assays with cell-free virus and T cells as targets, commonly used for evaluating the neutralizing titers in AIDS vaccine trials, can be misleading and do not represent a real-life situation.…”
Section: Neutralizing Antibodies In Serummentioning
confidence: 91%
“…This led us to propose that both HIV and HTLV-I may affect mucosal immunity (23,26). A series of subsequent studies using an in vitro model of sexual and transplacental HIV transmission has shown that although target epithelial cells, whether of intestinal or placental origin, seemed to lack a CD4 receptor, they, nevertheless, were susceptible to HIV if the virus was delivered by cell-cell contact (19,25,129). Studies from several labs around the world have confirmed these findings (153).…”
Section: Transmucosal Transmission Of Hivmentioning
confidence: 98%
See 1 more Smart Citation